Full text of "Economic, Social and Cultural Rights in China" (5): 3 (Xinhua News Agency - CEIS, 2005)
Conditions of housing and living environment have improved remarkably for both urban and rural residents, thanks to the ongoing reform to commercialize housing distribution. Back in 1994, work began to push the system of public accumulation funding for housing construction. By the end of 2003, the system had involved 60.45 million employees in cities and the funding had snowballed to 556.3 billion yuan by now, from which 174.3 billion yuan had been drawn for purchase of housing by its contributors or upon their retirement. Besides, banks had lent 234.3 billion yuan to 3. 27 million home buyers. In 1998, the government decided to encourage the building of housing affordable to the average wage earner while affording sufficient comfort and convenience. By 2003, construction had been completed on 477 million square meters of what is known as "housing inexpensive while good for practical use. " Also in 1998, work began to promote a low-rent housing system in Chinese cities to the benefit of poor families with overcrowded space to live in, and right now, the system has been instituted in 35 large and medium- sized cities. Living space now averages 23.7 square meters for city dwellers and 27.2 square meters for rural residents.